PENGARUH HARGA TRANSFER, KAPITALISASI MINIMAL DAN INTENSITAS MODAL TERHADAP AGRESIVITAS PAJAK - Sahira Zhafira Aghniya, (2023)
This research was conducted to analyze the effect of transfer pricing, thin capitalization, and capital intensity on tax aggressiveness. The object of this study is manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2019 - 2021, with a total sample of 45 companies. This study uses a quantitative method using panel data. This study used quantitative methods using panel data. The data analysis technique used is the panel data estimation selection test, classic assumption test, multiple regression test, and hypothesis test with a significance of 5%. The results of this study indicate that transfer pricing has no effect on tax aggressiveness , thin capitalization and capital intensity have negative effect on tax aggressiveness.